National and Transnational Paths of Latin American Jews : Modernity, Community, Society, and the State - Liwerant, Judit Bokser, (Jewish Identities in a Changing World ;, 2025)
The book studies Jewish life in Latin America through a dynamic past-present timeline. It combines the national, regional, and transnational dimensions by analyzing central crossing axes: the national within the diasporic, the transnational dialectically traversing both, and the national and regional dimensions developing in a global and interconnected Jewish world. Delving into the dilemmas and challenges that Modernity posed to Jews, this book emphasizes the practical and ideational responses it evoked. For Latin American Jews, this has involved moving from historical territories to new geographies, bringing with them the transmigration of worldviews and ideologies that were later re-signified.. The roots, displacements, embeddedness, and relocation of Jewish life are explored, shedding light on the richness and dilemmas of Jewish Modernity and Multiple Modernities. Thus, it critically analyzes membership criteria, social practices, and political participation, underscoring how visibility and agency in the public sphere were defined in different periods and contexts through the dyad belonging and Otherness. Its focus on Zionism and Mexico as a case study contributes to the field with original, in-depth research. With Diaspora, globalization, and transnationalism as an analytical framework, the book offers a unique and compelling insight into social and communal change and the multiple interactions of the contemporary Jewish world, sparking the curiosity and engagement of the academic audience and interested public.